2017
DOI: 10.3892/ol.2017.6698
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin, a dipeptidyl peptidase-4 inhibitor, suppresses CXCL5 and SDF-1 and does not accelerate intestinal neoplasia formation in ApcMin/+ mice fed a high-fat diet

Abstract: Abstract.The relationship between type 2 diabetes mellitus and intestinal neoplasia has been shown epidemiologically. A high-fat diet (HFD) is also known to promote insulin resistance, which is a risk factor for intestinal neoplasia. Dipeptidyl peptidase-4 (DPP-4) inhibitors are used in the clinic for the treatment of type 2 diabetes and also to prolong the effects of glucagon-like peptide-1 (GLP-1). However, since the intestinotrophic hormone GLP-2 and chemokines, such as CXCL5 and stromal cell-derived factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…suppressed the levels of plasma CXCL5 and CXCL12 in mice fed a HFD which could suggest a reduction in cancer risk in obese or diabetic patients (Fujiwara et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…suppressed the levels of plasma CXCL5 and CXCL12 in mice fed a HFD which could suggest a reduction in cancer risk in obese or diabetic patients (Fujiwara et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Dipeptidyl peptidase 4 (DPP-4) is a naturally occurring serine protease expressed on the cell surface and thoroughly known to regulate glucose metabolism. DPP-4 rapidly degrades glucagon-like peptide (GLP-1 and GLP-2), glucose-dependent insulin releasing polypeptide GIP [5], stromal-cell derived factor (SDF-2) [6], chemokine (C-C motif) ligand 5 (RANTES) [7], and eotaxin [8]. Among these specific substrates, incretin hormones secreted by intestinal cells are responsible for adequately controlling blood glucose levels [9].…”
Section: Introductionmentioning
confidence: 99%
“…We found only one clinical study conducted in 2018 on the risk of colon carcinogenesis; the study reported that there was no improvement in the risk of developing colon carcinogenesis by DPP-4 inhibitors [77,78]. In in-vitro studies conducted between 2000 and 2019, there were three reports that confirmed the tumor suppressing by DPP-4 inhibitors [79][80][81], on the contrary, one study reported that the tumor suppressing effect could not be confirmed.…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 86%